Kajian Studi Kelayakan Sungai Sail Untuk Ketersediaan Air Baku Di Kecamatan Bukit Raya Kota Pekanbaru - Septya Ardiani; Imam Suprayogi; Jecky Asmura (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The Regional Water Company (PDAM) has not been able to providing clean water in the city of Pekanbaru, one of which is the Bukit Raya subdistrict because of the many obstacles faced such as leaking pipes, the age of the pipe that is very old, and the quality of the Siak River water had been contaminated by heavy metals. So it is necessary to study the potential for surface water sources that could be developed, one of which is Sail River considered potentially to be used as a source of raw water. This study aims to determine the quantity of river discharge associated mainstay of Sail River, Sail river water balance and determine the quality of Sail River that can be used as a raw water source, in this case water providers to meet the needs of Bukit Raya subdistrict.The results of the calculation, 95% of the river discharge mainstay Sail River of 0,21 m3/sec. Clean water needs of domestic and non domestic in 2033 amounted to 0.283 m3/sec. Based on the amount of discharge is available on the river and the need for clean water is known Sail River water balance have deficit water amounted to -0,073 m3/sec. Results of laboratory tests of water quality in mind some of the parameters that does not comply with quality standards, such as pH, BOD, COD, DO, NH3, nitrogen, iron, sulfur as H2S, and total coliform. Therefore, to take advantage of Sail River as raw water treatment is required in advance.Keywords: Feasibility Study, Raw Water Availability, Sail River